STRATEGI PENGELOLAAN KELAS DALAM MENINGKATKAN KEDISIPLINAN DAN EFEKTIVITAS BELAJAR SISWA PADA MASA COVID-19 - Fitriana, Azizah Nur (Universitas Muria Kudus, 2024)
The COVID-19 pandemic is affecting the education sector, including in Indonesia. The government implemented social policies and distance education to prevent the virus. However, distance learning produces challenges for teachers and students, especially in terms of learning discipline and classroom management. This study aims to collect and analyze a number of different classroom management approaches that can be used during the COVID-19 pandemic to improve student discipline and increase learning efficiency. This study discusses how students can learn better, especially about environmental studies, with good classroom management. It also emphasizes the role of teachers in creating a good learning environment and encouraging students to learn independently. The study found that student learning outcomes are influenced by effective classroom management; to improve student behavior and engagement, classroom design and socialization should be improved. The COVID-19 pandemic shows the importance of engaging classroom management strategies.